Endoscopic ultrasound guided therapy of gastric varices: Initial experience in the Arab world (with video) - Alali, Ali A.; Hashim, Ahmad; Alkandari, Asma (Frontiers in Gastroenterology, 2022)
Background and objectives Gastric varices (GV) bleeding is a catastrophic complication of portal hypertension and is associated with significant morbidity and mortality. There are limited effective therapeutic interventions for the management of bleeding GV. Recently, EUS-guided therapy has been shown to be effective and safe intervention for such patients. However, there are no data to describe the feasibility and safety of EUS-guided therapy for GV in Arab population. The aim of this study is to describe our initial experience of EUS-guided therapy for GV in Kuwait. Methods A case-series of patients that underwent EUS-guided therapy for clinically significant GV. All patients underwent EUS-guided therapy including Cyanoacrylate (CYA) injection with or without coil embolization. Patients were followed post procedure to document GV obliteration and monitor for any adverse events. Results In total, 15 patients were included in this study (80% male) with mean age of 58±12 years. The main indication for therapy was active GV bleeding (53.3%) followed by secondary prophylaxis (33.3%). Most patients had GOV-2 (80%) with mean GV size of 24.9±7.9 mm. Combined EUS coil-CYA was used in most patients (80%), mean volume of CYA injected was 1.5±0.74ml and mean number coils used of 1.5±1.4. The technical success rate was 100% and all patients achieved GV obliteration after a median of 1 session (range 1-2). There were no major adverse events. Conclusion Among Arab population with portal hypertension, EUS-guided therapy is highly effective and safe option for the managements of clinically significant GV.